2020
DOI: 10.3389/fvets.2020.558793
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Different Indicators to Benchmark Antimicrobial Use Affect Farm Ranking?

Abstract: The need to reduce antimicrobial use (AMU) in livestock production has led to the establishment of national AMU data collection systems in several countries. However, there is currently no consensus on which AMU indicator should be used and many of the systems have defined their own indicators. This study sought to explore the effect of using different internationally recognized indicators on AMU data collected from Irish pig farms and to determine if they influenced the ranking of farms in a benchmarking syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…This emphasises the need to improve pig farmers’ knowledge of animal welfare and to ameliorate communication between stakeholders. Moreover, given that farmers’ perceive that AMU is generally low in Ireland, the implementation of on-farm monitoring systems at national level is fundamental because it will provide further data on the actual use, the potential associated cost and will improve the national benchmarking scheme recently started [ 80 , 81 ]. Finally, these findings are useful for national authorities as guidelines when proposing recommendations regarding prudent AMU on-farm and for the development of effective Irish policies and education strategies for its reduction.…”
Section: Resultsmentioning
confidence: 99%
“…This emphasises the need to improve pig farmers’ knowledge of animal welfare and to ameliorate communication between stakeholders. Moreover, given that farmers’ perceive that AMU is generally low in Ireland, the implementation of on-farm monitoring systems at national level is fundamental because it will provide further data on the actual use, the potential associated cost and will improve the national benchmarking scheme recently started [ 80 , 81 ]. Finally, these findings are useful for national authorities as guidelines when proposing recommendations regarding prudent AMU on-farm and for the development of effective Irish policies and education strategies for its reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Variations in the diversity of antimicrobials used depending on the species (which could impact total or class-specific nDDDvetCA's) and the proportion of antimicrobial classes used have been described elsewhere [53]. The DDDvet/PCU has been utilized in several AMU research studies [17,24,58] and has been useful when other input parameters (i.e., the days at risk) for other more popular dose-based indicators, nDDDvetCA/1000 animal-days at risk, as above (TI 1000 ), or the alternate indicator, TI 100 , are unavailable. Ultimately, for our study, the nDDDvetCA/kg animal biomass was selected for other study objectives (e.g., AMU-AMR association) and was preferred over nDDDvetCA/PCU to reduce the analytic burden of obtaining denominator data (i.e., average weight at treatment).…”
Section: Amu Indicator For Comparison Of Use Between Speciesmentioning
confidence: 99%
“…These include the European Surveillance for Veterinary Antimicrobial Consumption's (ESVAC) mg of antimicrobial active ingredient per population correction unit (mg/PCU), [14] used for the harmonized reporting of AMU in the European Union/European Economic Area (EU/EEA), and the OIE's mg/kg animal biomass [15], used for reporting the global AMU data. Dose-based indicators such as Treatment Incidence [TI 100 and TI 1000 ], DDDvet per PCU and other derivatives of these indicators (e.g., annualized estimates such as DDDvet/Year) are also utilized by regional and national AMU monitoring systems and in AMU research [13,[16][17][18][19][20][21][22][23]. Unfortunately, there is no single AMU metric or indicator that can address all the objectives of an AMU surveillance program or study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…O'Neal at al. reported that by comparing the monitoring results using DDD values established by the EMA, Denmark and the Netherlands, different DDD systems produced different consumption patterns even though the underlying data for each was identical [24].…”
Section: Plos Onementioning
confidence: 99%